ANALISIS NILAI RELIGIUS DAN NILAI BUDAYA PADA FILM “BUYA HAMKA” SERTA PEMANFAATANNYA SEBAGAI BAHAN AJAR DI SMA - Nuraini; Trisnawati; Saraswati (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study explores the religious and cultural values contained in the film Buya Hamka by Alim Sudio and analyzes its potential use as teaching material in senior high schools. The film not only depicts the biography of a renowned Indonesian scholar, writer, and cultural figure but also presents strong moral messages, Islamic teachings, and local wisdom that align with character education. The research is motivated by the importance of maintaining religious and cultural values amid globalization and modernization, which can threaten the local identity of young generations. This study introduces a new perspective by integrating religious and cultural values from a biographical film into character-based learning, a topic rarely discussed in previous studies. The theoretical framework includes the concept of literature as a reflection of life, religious values such as worship, ruhul jihad, morality, exemplary conduct, trustworthiness, and sincerity, as well as cultural values covering life necessities, truth, ancestry, and sources of life. Using a descriptive qualitative method with content analysis of dialogues, scenes, and narration, the study concludes that Buya Hamka can serve as appropriate teaching material under the Merdeka Curriculum, especially for expository texts. Its use in learning is expected to enhance critical literacy, strengthen the Pancasila Student Profile, and develop students’ spiritual and cultural awareness.